2022
DOI: 10.3389/fphar.2022.944893
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle and apoptosis related and proteomics-based signaling pathways of human hepatoma Huh-7 cells treated by three currently used multi-RTK inhibitors

Abstract: Sorafenib, lenvatinib and regorafenib, the multi-RTK inhibitors with potent anti-angiogenesis effects, are currently therapeutic drugs generally recommended for the patients with advanced hepatocellular carcinoma (HCC). To date, however, there have been no published studies on the mechanism underling differential effects of the three drugs on HCC cell proliferation, and the proteomic analysis in HCC cell lines treated by regorafenib or lenvatinib. The present study for the first time performed a direct compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…A concentration-dependent arrest of the cell cycle in the G0/G1 phase was found in parallel with a decrease in the S-phase fraction of the cells after treatment with DAS, ERL, REG, and SOR ( Figure 3 A–D). This is in line with several reports showing G0/G1 mediated cell cycle arrest in various human normal and cancer cell lines exposed to TKIs [ 33 , 38 , 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…A concentration-dependent arrest of the cell cycle in the G0/G1 phase was found in parallel with a decrease in the S-phase fraction of the cells after treatment with DAS, ERL, REG, and SOR ( Figure 3 A–D). This is in line with several reports showing G0/G1 mediated cell cycle arrest in various human normal and cancer cell lines exposed to TKIs [ 33 , 38 , 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
“…TKIs are homologs of adenosine triphosphate (ATP), which competitively occupy the ATP-binding site of protein tyrosine kinases (PTKs) and thus block PTK-mediated signaling pathways in cancer cells, thereby inhibiting their growth and proliferation [ 2 ]. Notwithstanding the wide variety of TKI targets, the suppression of cancer cell proliferation by blocking cell division in the G0/G1 phase of the cell cycle is one of the most prevalent anti-tumor mechanisms of numerous TKIs, including DAS, ERL, NIL, SOR, and REG [ 33 , 38 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate a high degree of ischemia in the tumors from animals treated with both NP formulations, although there were no significant differences between them. Moreover, lenvatinib is an inhibitor of multiple receptor tyrosine kinases capable of inducing early processes of apoptosis and necrosis in Huh-7 cells [43]. Furthermore, it has been described that PLGA NPs loaded with temozolomide conjugated with cetuximab, designed to target cancers that overexpress EGFR, were able to promote late processes of apoptosis and necrosis compared with PLGA NPs loaded with temozolomide [44] Although our Ki67 data did not reveal significant differences between both formulations in the tissue areas far from the necrotic areas of the tumors, we must highlight that in the analysis of cells with typical morphologies of nuclear apoptosis (condensation and fragmentation), as well as the morphology of karyolysis, we demonstrated that the tumoral tissues obtained from animals treated with decorated nanoparticles showed a greater percentage of these cell types compared with those treated with undecorated nanoparticles.…”
Section: Discussionmentioning
confidence: 99%